Acute Myeloid Leukemia in an Infant with t(8;19)(p11.2;q13) Translocation: Case Report and a Review of the Literature - Ashley C. Eason; Silvia T. Bunting; Jess F. Peterson; Debra Saxe; Himalee S. Sabnis (Case Reports in Hematology)
Acute myeloid leukemia (AML) patients with t(8;16)(p11.2;p13) constitute a small subgroup with a distinct genetic and clinical profile. We present a unique case of a female infant with monocytic AML associated with t(8;19)(p11.2;q13.3), a rarely reported variation of t(8;16)(p11.2;p13). The patient presented with leukemia cutis and demonstrated erythrophagocytosis in the diagnostic bone marrow. She responded well to standard AML chemotherapy and is currently in remission. Here, we highlight her case as the youngest AML patient with t(8;19) described in the literature, discuss the significance and prognostic implications of this genetic variant, and review 8p11.2 fusion proteins in AML.